BREAST CONDITION IN WOMEN WITH ENDOMETRIAL HYPERPLASIA DURING THE PERIMENOPAUSE - Z.Z.Askarova; D.A. Aliyeva; M.Z. Kurbaniyazova (Scholar Express Journals, 2023)
We observed women in perimenopause with endometrial hyperplasia who underwent digital mammography, according to the results of mammographic examination, benign changes were found in 47% of women with GE, benign changes were found in 29.4% of women that require re-examination after 6 months, and in 8, 2% of women with GE had signs suspicious of breast cancer and were referred for biopsy and histological examination.
Keywords: mammography; endometrial hyperplasia